Multiple Small Coronary Artery Fistulas Emptying into the Left Ventricle: A Rare but Challenging Problem - Omar Kahaly; Konstantinos Dean Boudoulas (Case Reports in Medicine)
A coronary artery fistula (CAF) is an abnormal communication between a coronary artery and a cardiac chamber or a great vessel. CAFs are rare based on coronary arteriography and when found they most often empty into the right ventricle and atrium and less often into the high pressure, low compliance left ventricle (LV). A patient who presented with atypical chest pain and was found to have multiple small CAFs originating from the ramus intermedius coronary artery and emptying into the LV is presented. This case highlights the challenges in providing an appropriate therapy for multiple small CAFs emptying into the LV.